PIJAT TUI NA TERHADAP PENINGKATAN NAFSU MAKAN PADA ANAK DENGAN USIA 1-3 TAHUN DI POSKESDES KUTAPANDAN - Putri, Sartika Dwi Yolanda; Wijayanti, Adhika; Apriani, Miftah; Arahman, Suaidy; Yulia, Yulia (Jurnal Kesehatan Abdurrahman, 2025)
This study aims to determine the effect of Tui Na massage on increasing appetite in children aged 1-3 years at the Kutapandan Village Health Post. The research design used was Pre Experiment using One Group Pre Test – Post Test Design. The research sample was children aged 1-3 years with decreased appetite in the Kutapandan Village Health Post area. The data collection instrument is the CEBQ questionnaire. Sampling used Purposive Sampling. The results of statistical tests using the Paired T Test with α: 0.05 obtained t = -4.168, ρ value 0.001. The research results showed that appetite before the Tui Na massage had an average value of 109.20 and the average value after the Tui Na massage was 114.12. This shows that there is a significant increase in children's appetite after Tui Na massage. In conclusion, Tui Na massage is effective in increasing appetite in children aged 1-3 years at the Kutapandan Village Health Post.